Efecto del origen del material de siembra y el sistema de cultivo en la severidad e incidencia del anublo bacterial, el anublo fungoso y el superalargamiento de la yuca - Laberry, R.; Lozano, J.C. (1990)
Data on max. and min. severity of attacks by Xanthomonas campestris pv. manihotis, Choanephora cucurbitarum, and Sphaceloma manihoticola were gathered on commercial plantations located in 4 regions of Sucre, Colombia. Regional clones Venezolana and Preta were used. In the region of Bongo, neither X. campestris pv. manihotis nor C. cucurbitarum were observed; S. manihoticola was absent in the region of Hato Nuevo. These regions are therefore considered apt for cassava cultivation. The max., min., and total severity means, as well as the percentages of incidence on diseased plantations, were higher when cuttings from meristem culture were used as planting material. Severity indexes and percentages of incidence of S. manihoticola were higher in multiclonal lots than in monoclonal lots; susceptible clones should not be planted next to intermediately resistant clones, since the severity indexes in the latter may increase. The lowest disease incidence and severity were observed in cassava intercropped with maize, since the maize acted as a live barrier avoiding spores of the causal agent to be deposited on susceptible host plant tissues. This cropping system is recommended for areas where S. manihoticola is endemic. (CIAT)